(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2019)
A healthy snack based on corn (Zea mays L.) and beans (Phaseolus vulgaris L.) was developed, taking into account both consumer preference and nutritional value. To enhance its nutritional value, soy flour (Glycine max L.) was added. The aim of this study is to formulate a snack with the highest amount of soy flour without being perceived by future consumers. Using a sensory analysis technique called Detection Threshold Test, the maximum amount of soy flour that can be added to the product without being detected by the user was determined. Five panelists were involved, and five products with different concentrations of soy flour (10%, 15%, 20%, 25%, and 30%) were developed. A table was created with the various concentrations and the percentage of panelists that perceived the soy flavor at each concentration. Using Linear Regression, the equation of the line for the percentage of the product as well as the percentages of panelists who perceived it were obtained. It was found that the maximum concentration of soy flour to be used without perceiving its flavor is 12.502% of the total raw materials of the snack. To confirm the value obtained, another research will be conducted subsequently by preparing the product with the obtained formulation and presenting it to a tasting panel.